according to the question, x – 3y + 2z + (-4x + 9y – 11z) -3x + 6y -9z now, -3x + 6y -9z – (3x – 4y -7z) -3x + 6y -9z -3x + 4y + 7z -6x + 10y – 2z is the required answer . Reply

Answer: [tex]\huge\mathfrak\purple{Answer}[/tex] = x – 3y + 2z + (-4x) + 9y – 11z – (3x – 4y – 7z) = x – 3y + 2z – 4x + 9y – 11z – 3x + 4y + 7z = x – 4x – 3x + 2z – 11z + 7z + 9y + 4y = -3x – 3x + 2z – 4z + 13y = -6x – 2z + 13y Step-by-step explanation: Hope this helps you. # By Sparkly Princess Reply

according to the question,

now,

is the required answer .

Answer:[tex]\huge\mathfrak\purple{Answer}[/tex]

= x – 3y + 2z + (-4x) + 9y – 11z – (3x – 4y – 7z)

= x – 3y + 2z – 4x + 9y – 11z – 3x + 4y + 7z

= x – 4x – 3x + 2z – 11z + 7z + 9y + 4y

= -3x – 3x + 2z – 4z + 13y

= -6x – 2z + 13y

Step-by-step explanation:Hope this helps you.

#BySparklyPrincess